Multistrange baryon production in high energy electron-proton collision / Nooratikah Mohammad Nasir - Nooratikah , Mohammad Nasir (2018)
A search for Ξ−‘s decaying to Λ combinations is carried out to calculate the total cross sections in electron-proton collisions at HERA. The analysed data were collected using the ZEUS detector during the running period of 2002-2007 with an integrated luminosity of 323 pb-1. The data analysis was done using online and offline analysis at center-ofmass energy of √s = 318 GeV. Strange and multistrange baryon production phenomenology such as String Model is reviewed, as it is not fully understood yet. The cross section carried out has been compared with ARIADNE Monte Carlo (MC) simulation predictions.